DEGRADASI SIKAP MENTAL SPIRITUAL REMAJA HINDU PADA PELAKSANAAN SIVARÂTRI DI DESA PENGIANGAN KECAMATAN SUSUT KABUPATEN BANGLI (KAJIAN PENDIDIKAN HINDU) - Gusti Ayu Melani; I Ketut Sudarsana (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
Any physical necessity as well as material has been successfully developed by humanbeing which is supported by the sophistication of technology. However, it is followed by theconsequences of moral degradation struck all over the country. By the increasing of westernculture’s influence, the moral degradation seems to be no longer a serious problem. Similarly,all aspects of life including religious rituals become less sacred. Balinese Hindu teenagers morelikely disrespect the sanctity in practicing the religious rituals by doing inappropriate attitudeand action such as; the way they pray, how to dress, the behavior before and after praying likegoing to play at the beach or to other places for fun. Such deviant behaviour is a commonoccurrence among Balinese Hindu teenagers in participating religious ceremony, such ascelebration of Sivarâtri. Implementation of Sivarâtri aims as a medium to embed spiritual valuesof Hindu to the followers and implement them in daily life. In fact, the celebration of Sivarâtri isused as an excuse to have fun. Hindu teenagers in Pengiangan Village make use of Sivarâtrimoment as a venue to seek the enjoyment.Jagra which supposedly make people conscious, on the contrary is neglected by Hinduteenagers due to the overwhelmed desire. The inability to control themselves in daily lifeinteraction, accordingly marriages occur as the consequence of moral degradation. Societyseemingly is not attentive to the spiritual behaviors degradation of Hindu teenagers in carryingout religious activities. Moreover, the early marriages which is due to promiscuity taken forgranted. This research was conducted in Pengiangan village of Susut District of Bangli Regency.The purpose of this study is to know : 1). The form of mental spiritual degradation of Hinduteenagers on Sivarâtri, 2). The causative factors of mental spiritual degradation of Hinduteenagers on Sivarâtri, 3). The efforts for anticipating mental spiritual degradation of Hinduteenagers on Sivarâtri in Pengiangan village of Susut District of Bangli Regency.Keywords: Degradation, Mental Spiritual Attitude, Hindu Teenagers, and Sivarâtri.